Sosialisasi dan Pendampingan Kadet S1 Sejarah Militer Universitas Pertahanan Pada Usulan Gelar Pahlawan Nasional Di Fakultas Ilmu Budaya Universitas Indonesia - Ramsi, Oktaheroe; Subiantoro, Yudi; Manurung, Hendra; Pertiwi, Yuliana Anggun; Pannyiwi, Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
This article describes how the proposal for state awards given by the President to every Indonesian citizen or someone who has died is known as the awarding of the title of national hero. On November 20, 2024, 25 cadets of the Military History Bachelor's Degree from the Faculty of Defence Strategy, Indonesian Defence University accompanied by the Head of the Study Program, lecturers, and staff attended the 'Seminar on the Proposal for the Title of National Hero in the Name of Wongsonegoro' at the Faculty of Cultural Sciences, University of Indonesia. Mr. Wongsonegoro was born on April 20, 1897, and died on March 4, 1978. He was Deputy Prime Minister of Indonesia in the Ali Sastroamidjojo I Cabinet from 1953 to 1955 and Minister of Education and Culture of Indonesia from 1951 to 1952. In addition, during the preparation for Indonesian independence, he also joined the Investigating Committee for Preparatory Work for Indonesian Independence (BPUPKI), representing the city of Surakarta, together with Wuryaningrat, Sosrodiningrat, and Radjiman Wedyodiningrat. BPUPKI was an agency formed by Japan to prepare for Indonesian independence. This title is given to those who have rendered services and dedication and fought for the nation and state. This title is also given to those who have rendered services, dedicated, and fought for the nation-state. It revealed that the proposal to grant the title of National Hero to Mr. Wongsonegoro is a form of state appreciation given by the President to Indonesian citizens or someone who has died, for acts of heroism, devotion, philanthropy, and extraordinary eternal work to the nation and state.